Transanal endoscopic microsurgery: results of the first 50 cases - SAMALAVIČIUS, Narimantas Evaldas; KILIUS, Alfredas; PETRULIS, Kęstutis; LETAUTIENĖ, Simona; GRIGIENĖ, Rūta; BRIEDIENĖ, Rūta; MIŠEIKYTĖ-KAUBRIENĖ, Edita (Acta medica Lituanica, 2012)
The aim of the study was to share the experience and first results of implementation of transanal endoscopic microsurgery (TEM) technique for the removal of rectal adenomas, early rectal cancer or rectal stricture in the Center of Oncosurgery, Oncology Institute of Vilnius University.Materials and methods. From October 2009 to October 2011, a total of 50 patients underwent TEM for rectal adenomas, early rectal cancer or rectal stricture. The patients were 25 women and 25 men, 31 to 87 years of age (average 65 years). Rectal lesions were from 0.9 to 7.0 cm in diameter, 3–13 cm from the anal verge. Full thickness excision with 1 cm safety margin was achieved in all cases except two (mucosal excision), followed by closing of the rectal wall defect in one-layer running monocryl 3.0 suture using silver clips. In one case (TEM was performed for T2 rectal cancer), abdominal cavity was penetrated and two-layer closure was preferred.Results. In these series of 50 patients there was 1 (2%) complication (cystitis). No postoperative exitus occurred. The hospitalisation period ranged from 2 to 13 days (average 6 days). Final histology revealed 30 (60%) tubular or villous adenomas, 6 (12%) carcinomas in situ (pTis), 7 (14%) T1, 4 (8%) T2 cancers, and well-differentiated neuroendocrine tumors in 3 (6%) were diagnosed. One patient underwent open partial TME in pT1 group; the tumor was in the upper third of rectum and preoperatively evaluated as pTis disease. In two cases (pT1 group) lymphovascular invasion was present on final pathology, so they were offered a postoperative adjuvant chemoradiotherapy. Other 4 patients in T1 group are under surveillance.All 4 patients with T2 lesions were offered adjuvant chemoradiotherapy, one patient refused further treatment.Conclusions. TEM is an alternative for transanal excision of rectal adenomas and early rectal cancer. Further follow-up is necessary to evaluate the recurrence rate of cancer in invasive cancer patients group.
Keywords: rectal polyp; rectal cancer; transanal endoscopic microsurgery (TEM)